If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k/4+3=14
We simplify the equation to the form, which is simple to understand
k/4+3=14
We move all terms containing k to the left and all other terms to the right.
+ 0.25k=+14-3
We simplify left and right side of the equation.
+ 0.25k=+11
We divide both sides of the equation by 0.25 to get k.
k=44
| X+1+4=6x | | 9n=n+96 | | .3(60)+.2(40)=x(60+40) | | 5c-4c-2c+1=8c+2 | | -3(5z+24+2)=2(-2z+3)-4 | | 6n=2n+60 | | 5x^2+52x+20=0 | | -22=-2(b+3) | | 12x-3=4x+5 | | 4x+7=.12+2x | | M+3=b | | 60(.3)+40(.2)=x(60-40) | | 23-3x=46 | | 6.06x+30.3=60.6 | | 60(.3)+40(.2)=x(60+40) | | -3x+(-5)=-32 | | 30x-12=28x-28 | | 6x+17y=250 | | 3+2x+5-6x=-1+7x-9 | | -10x=5x+45 | | 31=4u+7 | | n^2-n-148=0 | | 4(x-3)=-6(x+2)+14 | | -4x-5=-6x+1 | | (2+x)+59=90 | | -13x=286 | | 11x+5=16x+76 | | 80=11x+9x | | 3r+2(5r-3)=7 | | 20x-5-18x+2=13x-9-11x+17 | | 1.6x+15(2.80)=2(x+15) | | 11x+5=16+76 |